2019
DOI: 10.1021/acssensors.9b00413
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Electrochemiluminescence of Silver Nanoclusters for microRNA Detection

Abstract: Surface plasmon-enhanced electrochemiluminescence (SPEECL) with excellent sensitivity and simplicity has attracted increasing attention. In this work, we reported a novel SPEECL with DNA templated silver nanoclusters (DNA-AgNCs) as ECL emitters and gold nanoparticles (AuNPs) as localized surface plasmon resonance (LSPR) source. The SPEECL with DNA-AgNCs as ECL luminophores possessed low toxicity and avoided the labeling process, which is favorable for its further sensing application. In addition, by investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“… 35 The biosensor that combines cyclic amplification with hairpin DNA detects attomolar miRNA via surface plasmon-enhanced electrochemiluminescence. 36 The gold nanoparticle with an RNA three-way junction motif can sense miRNA using electrochemical surface-enhanced Raman spectroscopy. 37 The photoelectrochemical biosensor, based on a MoS 2 /g-C 3 N 4 /black TiO 2 heterojunction as the photoactive material and gold nanoparticles carrying Histostar antibodies for signal amplification, captures miRNA that leads to horseradish peroxidase (HRP) immobilization, whose insoluble products in the electrode reduce photocurrent.…”
Section: Diagnostic Approaches To Covid-19mentioning
confidence: 99%
“… 35 The biosensor that combines cyclic amplification with hairpin DNA detects attomolar miRNA via surface plasmon-enhanced electrochemiluminescence. 36 The gold nanoparticle with an RNA three-way junction motif can sense miRNA using electrochemical surface-enhanced Raman spectroscopy. 37 The photoelectrochemical biosensor, based on a MoS 2 /g-C 3 N 4 /black TiO 2 heterojunction as the photoactive material and gold nanoparticles carrying Histostar antibodies for signal amplification, captures miRNA that leads to horseradish peroxidase (HRP) immobilization, whose insoluble products in the electrode reduce photocurrent.…”
Section: Diagnostic Approaches To Covid-19mentioning
confidence: 99%
“…The ECL signal and corresponding strength analysis indicated that the background ECL signal of the bare GCE and DNA-modified electrodes were extremely low (curves a−c). 36 With the implementation of in situ synthesis of AgNCs, the ECL signal of the electrode without a target miRNA displays no significant change from the background (curve d). In the presence of a target miRNA, the electrode displayed evidently enhanced ECL responses (curve e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Scheme , the versatile probe was designed with RNA splice sites and sulfhydryl functional groups then modified on a AuNP-coated GCE. Before miRNA detection, the commonly used sealant MCH was filled into spaces on the electrode to prevent nonspecific adsorption. , In order to detect the target miRNA, two corresponding auxiliary DNA chains that form compound DNAzyme structures with the probe and target were added to the solution to be tested. Target myocardial miRNA and auxiliary strands (component A and component B) form circular structures, which form DNAzyme on the probe and continue cutting the rA sites.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, several routes for the synthesis of AgNPs have been reported for the obtention of different particle sizes ranging from 5 to 100 nm 13 and even larger than 100 nm 14 . Interestingly, it has been demonstrated that some antibacterial 13 , optical 15 , and catalytic 16 properties of AgNPs are significantly enhanced for particle sizes smaller than 15 nm (sub-15 nm). Thus, despite the high surface area and tendency to agglomeration, aggregation, and/or dissolution processes 17 , the obtention of highly stable sub-15 nm AgNPs under controlled conditions has attracted great interest from the scientific community.…”
Section: Introductionmentioning
confidence: 99%